Desenvolvimento de um e-commerce com código open source - Sendeski, Lucas Tondo (2019)
With increasing numbers of people adopting e-commerce for product acquisition, many companies needed to develop new strategies to win new customers, build on existing ones, and optimize their sales. Therefore, an online sales platform proposes a facility for the customer to make purchases, optimizing the company's relationship with customers and unifying all customers in one place. In this work an e-commerce was developed using tools of development with open code. The solution developed allows for easy control for the e-commerce administrator and easy maintenance of the code for the developer involved.